The Western North Atlantic region - Vogt, Peter R.; Tucholke, Brian E. (Boulder, Colorado Geological Society of America Inc., 1986)
"One of the synthesis volumes of the Decade of North American Geology Project series"--P. 2.Includes bibliographies and index
Keywords: Geology -- North Atlantic Ocean; Paleoceanography -- North Atlantic Ocean; Geophysics -- North Atlantic Ocean; Geology; Mines and mineral resources -- North Atlantic Ocean